Anthropometric, lifestyle and parental characteristics associated with the prevalence of energy intake misreporting in children: the GRECO (Greek Childhood Obesity) study. Issue 7 (18th March 2015) - Farajian, Paul; Bountziouka, Vassiliki; Risvas, Grigoris; Panagiotakos, Demosthenes B.; Zampelas, Antonis
Abstract : The objectives of the present study were to identify childhood energy misreporting, and evaluate characteristics that are associated with its prevalence in a nationwide cross-sectional sample of Greek schoolchildren. Under the context of the GRECO (Greek Childhood Obesity) study, data from a total of 4547 children aged 10–12 years and 2318 parents were included in the analysis. Anthropometric, lifestyle and parental characteristics plus psychological concerns were investigated in relation to the prevalence of energy misreporting. Of the included children, 36 % were classified as energy under-reporters and 16 % as over-reporters. Multinomial logistic regression analysis revealed that the most important predictors of energy under-reporting (URP) were children's BMI (OR 1·11, 95 % CI 1·09, 1·14) and weight satisfaction (OR 0·87, 95 % CI 0·78, 0·97). In the case of energy over-reporting (ORP), children's BMI (OR 0·87, 95 % CI 0·84, 0·90), meal and snack consumption frequency (OR 1·52, 95 % CI 1·32, 1·75), female sex (OR 0·65, 95 % CI 0·45, 0·90), and maternal education (OR 0·95, 95 % CI 0·91, 0·99) remained as significant predictors. Additionally, parental perception that the body weight of their children was normal reduced the odds of URP (OR 0·69, 95 % CI 0·48, 0·99) and ORP (OR 0·53, 95 % CI 0·31, 0·93). In conclusion, the present study confirms that the issue of URP and ORP in childhood populations is evident and quite serious. Although there are no definite guidelines on how to use data obtained from misreporters in an epidemiological dataset, validity of reported energy intake seems to be influenced by children's BMI and weight satisfaction, as well as by parental perceptions regarding their children's weight.